THE EFFECT OF FERTILIZER BOKASHI SLUDGE BIOGAS LEAF GAMAL (GLIRICIDIA SEPIUM) WITH DIFFERENT LEVELS ON THE EARLY GROWTH OF LAMTORO TARRAMBA PLANT AGED 6 WEEKS - Lambu Emu; I Made Adi Sudarma (Journal of Innovation Research and Knowledge, 2023)
This study aims to determine the effect of giving bokashi sludge biogas from gamal leaves with different levels on the growth of the lamtoro tarramba plant. The experimental design in this study used a completely randomized design (CRD) to make 20 experimental units using 5 treatments and 4 replications. The treatments used were P0 (control) without fertilizer application, P1 (250) grams, P2 (500) grams, P3 (750) grams and P4 (1000) grams. The results of this study showed that the application of bokashi sludge biogas and gamal leaves fertilizer had a significant effect (P<0.05) on the height, stem diameter and number of compound leaves (strands) on the lamtoro plant. It can be concluded that offering bokashi sludge biogas and gamal leaves up to a level of 750 grams is able to give the best results in the initial growth of lamtoro tarramba.